2021
DOI: 10.1002/isaf.1487
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting spot prices of agricultural commodities in India: Application of deep‐learning models

Abstract: Food price fluctuations can impact both producers and consumers. Forecasting the prices of the agricultural commodities is of prime concern not only to the government but also to farmers and agribusiness firms. In developing countries like India, manage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Since the financialization of products, several studies have examined how products are linked together (Rl and Mishra, 2021)). Products markets need an understanding of oil and energy products fundamentals (Umar et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the financialization of products, several studies have examined how products are linked together (Rl and Mishra, 2021)). Products markets need an understanding of oil and energy products fundamentals (Umar et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fishe et al (2014) analyze the daily data of several agricultural futures positions to confirm the positive correlation between price changes and the positions of managed money firms. Additionally, financial traders are seen to reduce long positions to absorb risk during crisis (Singleton, 2014; Manogna and Mishra, 2021b). Creti et al (2013) investigate the correlation between S&P 500 and commodities using Dynamic Conditional Correlation-Generalized AutoRegressive Conditional Heteroscedasticity (DCC-GARCH) model for 25 commodity spot prices to reveal the consolidated linkage between stock and commodity markets when financial markets are stressed.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Common econometric models for commodity price forecasting include the autoregressive moving average, vector autoregressive, and vector error correction models. Recently, machine learning techniques (Bayona‐Oré et al, 2021), such as the neural network (Fang et al, 2020; Ribeiro & Oliveira, 2011), deep learning (Manogna & Mishra, 2021), extreme learning (Kouadio et al, 2018), genetic programming (Ali et al, 2018), support vector regression (Harris, 2017; Li, Chen, et al, 2020), K‐nearest neighbor (Gómez et al, 2021), multivariate adaptive regression splines (Dias & Rocha, 2019), random forest (Gómez et al, 2021), decision tree (Harris, 2017), ensemble (Fang et al, 2020), and boosting methods (Gómez et al, 2021), have shown great potential for forecasting of prices and yields of coffee (Kouadio et al, 2018), corn (Xu & Zhang, 2021), cotton (Ali et al, 2018; Fang et al, 2020), oats (Harris, 2017), soybeans (Li et al, 2020; Ribeiro & dos Santos Coelho, 2020), soybean oil (Li, Chen, et al, 2020), sugar (Ribeiro & Oliveira, 2011), and wheat (Fang et al, 2020; Gómez et al, 2021). In particular, previous studies show that the neural network has great potential to forecast economic and financial time series, which tend to have certain nonlinearities (Wang & Yang, 2010; Yang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Parot et al (2019) suggest the combination of the neural network model, vector autoregressive model, and vector error correction model for improving forecast accuracy from an individual model for EUR/USD exchange rate returns. R. L. Manogna and A. K. Mishra (2021) examine the price forecasting problem for the cotton seed, castor seed, rape mustard seed, soybean seed, and guar seed traded in National Commodity and Derivatives Exchange in India through deep‐learning neural networks. They find that the long short‐term memory neural network outperforms the time‐delay neural network and ARMA model.…”
Section: Introductionmentioning
confidence: 99%